Social Intervention for the Hard Core Poor: An Islamic Perspective - Marican, Sabitha; Ab Rahman, Asmak (2010)
This paper will focus on social intervention for the Muslim hard core poor. Social intervention is defined as the planned human activity that intervenes in and possibly alters the social environment. This study was conducted on the hard core poor whereby data was collected through a questionnaire using non-random sampling of 294 respondents from all states in Malaysia. The objective of the study is to determine the different types of aid received by the hard core poor and its implication on the state of their welfare. Findings indicate that a majority of the respondents received help in various forms from the government and only a small number is self-dependent. From an Islamic perspective, aid to the poor in a community can be channelled through various means, be it through government institutions or through individuals. Hence, this paper will cover various means of Islamic social intervention which address aspects of human welfare such as food, medical care, education and employment, towards productive community development.